Kajian Efektivitas Pembiayaan KUR Mikro Dalam Pengembangan UMKM di Bank Syariah Indonesia (Studi Kasus di BSI KCP Bogor Pomad) - Anisa, Norna; Hubeis, Musa; Palupi, Nurheni Sri (Institut Pertanian Bogor, 2023)
The Micro, Small, and Medium Enterprises (MSMEs) sector still faces several issues, such as a lack of capital for business development and limited access to financing from the banking sector. MSMEs play a crucial role in the Indonesian economy, contributing to 61.07 percent of the Gross Domestic Product (GDP) and employing 97 percent of the workforce. One of the government programs aimed at improving access to financing for MSMEs through financial institutions with a guarantee scheme is the People's Business Credit (KUR). This study aims to (1) identify the characteristics of MSMEs, (2) analyze the effectiveness level of KUR financing, (3) analyze the relationship between business characteristics and revenue growth, and (4) analyze customer satisfaction with these services. The methods used include descriptive analysis, validity reliability, cross-tabulation, chi-square, and Importance Performance Analysis (IPA). The results of the study indicate that out of 40 respondents who were customers of KUR financing at BSI KCP Bogor Pomad, the majority of them were engaged in trading and their businesses were located within a distance of 0.5 km-5 km. Their business objectives were primarily focused on working capital needs. After obtaining KUR financing from BSI KCP Bogor Pomad ranging from Rp10 million to Rp50 million, most customers reported monthly sales profits ranging from Rp1 million to Rp5 million, indicating significant assistance from KUR financing. Based on the analysis of the four aspects of financing effectiveness, the most dominant aspect is the accuracy in fund utilization with the highest value of 3.55. This finding is supported by three other variables: accuracy of financing amount (3.53), accuracy of margins (3.5), and accuracy of procedures (3.51). Regarding the relationship between business characteristics and revenue development, it was observed that the financing amount and the purpose of financing have a significant relationship (Chi-Square value <0.05). The results of the IPA analysis highlight the attributes that require improvement, which include clarity of the on-the-spot time for the notification of principle approval, speed of on-the-spot time for issuing the notification of principle approval, clarity of required costs, and speed of handling questions and complaints.